Fine Needle Aspiration Cytology of Lung Masses, benefits, precautions and complications. - Jameel, Mohammed J. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Pulmonary masses represent a great challenge for diagnosis. Fine Needle Aspiration Cytology (FNAC) is one of the diagnostic methods which was used since long time.Objectives: To concern on Fine Needle Aspiration Cytology of pulmonary masses regarding benefits, precautions and patient’s preparation to avoid possible complications.Patients and Methods: A prospective study is carried out from December 2008 to July 2015 on 45 patients presented with pulmonary masses to the Department of the thoracic and vascular surgery at Al-Yarmook teaching hospital and from the private sector. A Fine Needle Aspiration Cytology was done for them under local anesthesia as an outpatient procedure.Results: 40 patients (88.9%) got accurate results of diagnosis as different types of malignancies. Five patients (11.1%) got inconclusive results. No mortality reported. Complications like Pneumothorax was occurred in three patients (6.7 %), Haemoptysis in 14 patients (31%) and mild chest pain in 13 patients (29%).Conclusion: FNAC is relatively safe and valuable method to diagnose pulmonary mass lesions and to categorize them for better subsequent management either surgical or by chemotherapy but the patients must be prepared well and the doctor who intend to do FNAC either being trained to deal with possible complications or backed up with a thoracic unit.